Open edition books catalog - OpenEdition; MERCED-I (Mindanao Educational Resources for Curricular Enhancement and Development-Initiatives) on OER (Open Educational Resources). (Marseille, France Open Edition Center, 2020)
OpenEdition is a portal for electronic resources in the humanities and social sciences.
University Library (UL)
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Open education; Education, Higher; Humanities -- Electronic resources; Social sciences -- Electronic resources